Atypical femur fractures associated with bisphosphonates treatment: Retrospective single-center study (Annals of Medical Research, 2021)
Aim: Osteoporosis is a very common condition caused by an imbalance between bone production and resorption. The first-line treatment of osteoporosis and the most commonly prescribed medication group is bisphosphonates. In recent years, several researches have reported that atypical femur fractures are seen following long term bisphosphonate usage. However, time of usage is not clearly defined yet. Our purpose of this study was to unveil the correlation between long term bisphosphonate usage and atypical femur fractures.Material and Methods: Patients with a history of bisphosphonates treatment with atypical femur fracture were retrospectively analyzed. The collected data included patient demographics, the presence of trauma or history of the fracture, concomitant medical diagnoses, and history of bisphosphonates usage, type of bisphosphonates used, concomitant fractures, and other complications related to atypical femur fractures, mortalities.Results: Twenty-two patients were included. All patients were female, and the mean age was 79.36±8.71 (mean ± SD) years. Sixteen patients were taking alendronate for an average of 6.81±2.74 (mean ± SD) years while six patients were taking ibandronate sustained atypical femur fractures in a shorter time average of 4.66±1.49 (mean ±SD) years. Atypical femur fractures are started to be diagnosed after 3 years of usage with having peak numbers in forth year.Conclusion: Our study supports correlation between long term bisphosphonates usage and atypical femur fractures as reported in several studies. In the use of long-term bisphosphonates more than 3 years, care should be taken for atypical femur fractures, with investigating prodromal symptoms and performing radiological imaging.
Keywords: Bisphosphonates; atypical femoral fracture; osteoporosis treatment; fragility fractures